The Shoot Leadership Vs Babylonian Leadership: An Exposition of Isaiah 11:1-5, 11:1-22, 47:1-14 and its Implications for Leadership Today - Beidobak, Kostani; Najoan, Jemmy C. (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
The study of leadership is a subject that always arises in human life because of the changes and phenomena that continue to occur in leadership, especially in the context of the church. Problems that arise in the context of leadership in the church organisation make people turn to the Bible to find out the models of leadership that should be emulated or avoided. Using the exegesis method and supported by qualitative data from various sources, this article discusses the leadership models of the Shoot (Isaiah 11:1-5) and Babylon (14:1-22; 47:1-13). Based on the analysis, the leadership of the Shoot is based on the indwelling Spirit of God. Therefore, the Shoot has special skills in leading and the result is that his leadership is just and righteous, especially for the poor and oppressed. Furthermore, the success of the Shoot's leadership came about because it was based on righteousness and steadfast love. Babylon's leadership model, on the other hand, is prideful and relies on its own wisdom and understanding. This leads to a feeling of security to do evil. This also happened because it was supported by godless advisors. The result was total destruction for the nation itself. Today's modern leadership is expected to emulate the leadership of the Shoot and be careful not to emulate the leadership of Babylon